Critical Approaches to Human Rights and Communication for Social Change: An Emancipatory Dialogue - Rodríguez Arrieta, José Daniel (2026)
This paper establishes the links between the foundations, and, particularly, the objectives, of Critical Human Rights Approaches and Communication for Social Change. They are understood as alternative proposals that will, in turn, contribute to the understanding and potential of both fields, which have been mostly developed in Latin America. Identifying these common points reinforces thepotential for the establishment of emancipation strategies for various historically excluded sectors of society. These strategies aim to vindicate their human and fundamental rights through active communication strategies, ultimately leading to active participation in binding political decisions within their community and society at large.